Effects of spacing on the acquisition of explicit and implicit vocabulary knowledge: An approximate replication of Nakata and Elgort (2021) - Zheng, Guangliang; Nakata , Tatsuya; Clenton, Jon; Boutorwick, TJ (Studies in Second Language Learning and Teaching, 2026)
Research suggests that spaced learning, which incorporates intervals between repetitions of material, facilitates second language (L2) learning more than massed learning, where a given item is repeated multiple times without any intervening trials or time. Although prior studies have suggested that spacing enhances the acquisition of explicit knowledge, it remains unclear whether it aids the acquisition of implicit knowledge. The present study replicated Nakata and Elgort’s (2021) study to investigate how massing and spacing impact the acquisition of explicit and implicit vocabulary knowledge in L2. In the present study, 69 Japanese students learning (L2) English studied 48 pseudowords using either massed or spaced repetition. A meaning recall test (immediate and delayed) and a delayed meaning-form matching test assessed participants’ explicit knowledge. A semantic priming task (immediate and delayed) measured implicit knowledge. Posttest results showed that spaced learning led to better explicit vocabulary acquisition compared to massed learning. For implicit knowledge development, however, (a) neither schedule was effective, and (b) no significant difference was found between the two schedules.